L'archeosismologia in architettura Per un manuale - Arrighetti, Andrea (Strumenti per la didattica e la ricerca, 2015)
This volume deals with the very current issue of prevention and protection of the historical buildings from seismic risk, offering a methodology of investigation, called "archaeoseismology", developed within university environments and refined by several discussions with professionals and experts of the field. The text is not only intended for an audience with an archaeological background, but also for the different people operating in the field of cultural heritage and seismic risk, be these architects, restorers, structural engineers, historians or seismologists. The book, therefore, aims at acting as a first step towards the affirmation of a news discipline, analysing and enhancing its applicability and potential, and providing unpublished and indispensable data for the knowledge, enhancement and protection of cultural heritage.